Communication and the origins of personhood - Uygun Tunç, Duygu (Universitätsbibliothek Heidelberg, 2020)
This thesis presents a communicative account of personhood that argues for the inseparability of the metaphysical and the practical concepts of a person. It connects these two concepts by coupling the question “what is a person” (concerning the necessary conditions of personhood) with the question "how does one become a person"(concerning its genetic conditions). It argues that participation in social interactions that are characterized by mutual recognition and giving-and-taking reasons implied by the practical concept of a person is in fact an ecological and developmental condition for an entity to possess the kind of characteristics and capacities such as reflexive self-consciousness addressed by the metaphysical concept. The chief theoretical contribution of the dissertation research lies, accordingly, in demonstrating that an adequate metaphysical concept of a person has to make reference to the kind of social processes that are necessary for the emergence and development of the distinguishing attributes of persons among other moving, perceiving, desiring and cognizing agents. Methodologically, it undertakes an original philosophical analysis that is enriched by an interdisciplinary investigation of several notions and insights from semiotics, comparative and developmental psychology, cognitive science and anthropology. The main argument of the thesis is that one becomes a person through internally recreating a social, communicative process; namely, that of dialogical transformation of habits. We find the paradigmatic case of this social process in mutual persuasion. The internalization of this process in the form of an inner dialogue cultivates a social self that is in ongoing communication with the embodied, organismic self of uncritically habituated attitudes, convictions and desires. This inner dialogue can be conceived as a temporally extended process of self-persuasion, which is characterized by an ongoing strive for attaining higher degrees of self-control; that is, for achieving a more coherent alignment between our habits and the kind of person we would like to be. It starts with self-interpretation and self-evaluation, and culminates in the formation of higher-order desires that facilitate habit-change and novel habit formation in accordance with certain social, moral, aesthetical or intellectual categories and norms one comes to endorse. For this reason, self-induced, deliberate habit-change is also a process of appropriation or self-appropriation, through which we strive to cultivate habits of feeling, thinking, acting that we can deem more truly ours. The thesis demonstrates that the capacity for engaging in this kind of self-persuasion consists chiefly in the capacities for metasemiosis, perspective-taking, and for cultivating habits of reflexivity. It explicates how all these capacities have a social origin and ultimately a social function by showing that they all presuppose certain higher-order communicative patterns that arose through an evolutionary and cultural history, and develop through the internal reconstruction of these patterns as cognitive-semiotic processes. The thesis concludes that becoming a kind of being who can engage in self-persuasion, thus a person, consists ultimately in internalizing the patterns of communicative social interactions in the form of an ongoing auto-communication.
Keywords: Hochschulschrift